Stationary and periodic solutions of the operator Riccati equation under a random perturbation - Dorogovtsev, A. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Sufficient conditions are presented for the existence of stationary and periodic solutions of the operator Riccati equation under a random perturbation.